Investigation of the Shared Genetic Influences on Bipolar Disorder, Borderline Personality Disorder and Regional Brain Structures - Campbell, Megan (Department of Clinical Laboratory Sciences, 2022)
Background: The heritabilities of bipolar disorder (BD) and borderline personality disorder (BPD) are 80% and 65%, respectively, indicating substantial genetic contributions to both disorders. BD and BPD are often comorbid, and both disorders have a polygenic architecture. These variants are thought to subtly affect multiple pathways, associated with structural brain abnormalities commonly observed in patients with BD and BPD. Brain regions have been shown to be highly heritable and under distinct genetic influences. However, the overlap in genetic risk between BD and BPD and altered brain regions, respectively, has not yet been determined. Aims and Objectives: The aim of this project was to determine whether genetic risk for BD and BPD overlaps with genetic risk for altered brain regions. Methods: Genome-wide association study (GWAS) summary statistics for BD (Ncases=20,352; Ncontrols= 31,358), BPD (Ncase=998; Ncontrol=1,545), eight subcortical brain volumes (nucleus accumbens, amygdala, caudate nucleus, hippocampus, pallidum, putamen and thalamus) and intracranial volume (ICV) (N=27,087), and cortical surface area and thickness (N=37,479) were obtained. Pleiotropy and concordance were assessed using SNP-Effect Concordance Analysis. Conditional false discovery rate (cFDR) was used to condition BD and BPD GWAS results on genetic variants that influence brain regions. Linkage Disequilibrium Score Regression was used to examine genome-wide correlations between BD, BPD and brain regions. Mendelian randomization was used to test for causal associations between BD, BPD and each brain region, respectively. Results: There was evidence of significant pleiotropy and positive concordance between BD and BPD (ppleiotropy=5x10-4; pconcordance=1x10-6, OR=1.29). Significant pleiotropy was observed between BD and the thickness of several cortical regions and two gyri, namely the lateral occipital (p=2.25x10-5), pars triangularis (p=1.1x10-4), rostral anterior cingulate regions (p=2.18x10-4) and post central (p=7.9x10-6) and supramarginal gyri (p=1.45x10-7). Significant positive concordance was noted between BPD and thickness of the lateral occipital region (p=3x10-4; OR=1.02). After conditioning BD onto BPD and each regional brain GWAS, 171 additional variants were significantly associated with BD (FDR<0.05). Three additional SNPs were significantly associated with BPD when conditioned on thickness of the lateral orbitofrontal, lingual, precentral and supramarginal regions. Discussion: The findings here of genetic overlap between BD, BPD and altered brain structure, while novel, are consistent with previous work. The cFDR analyses, highlight synapse and neurotransmitter regulation as a key underlying mechanism between BD and altered brain regions. Further fine-grained delineation of the role of the environment in these relationships and the inclusion of non-European populations are critical next steps, as they may provide insight into risk factors, new areas of treatment and aid in early detection of at risk individuals.